Uji aktivitas antibakteri dari ekstrak metanol, fraksi heksan, fraksi etil asetat dan fraksi air daun kari (murraya koenigii (l.) Spreng) - Sagita, Desi; Khoirudin, Taufik; Netty, Netty (Tropharm (Trobosan Pharmacy); Vol 1 No 1 (2015): Tropharm (Trobosan Pharmacy), 2021)
Antibacterial activity of extracts and fractions of curry leaves against Staphylococcus aureus and Escherichia coli has been done. Methanol was used for the extraction of the curry leaves, extract methanol was fractionated using different solvent polarity ie n-hexane, ethyl acetate and water. Antibacterial activity of extracts and fractions were measured by the appearance zones of inhibition by diffusion methode. The result show, hexane fraction was more effective against S. aureus than extract methanol and ethyl acetate fraction. The antibacterial activity of methanol extract, hexane fraction and ethyl acetate fraction at concentration (100 ppm) showed maximum zone of inhibition (5.2, 6.6 and 5.3 mm, respectively) againt S. aureus. At concentration (250 ppm) showed maximum zone of inhibition (7.3, 8.8 and 6 mm, respectively). At concentration (500 ppm) showed maximum zone of inhibition (9, 10.8 and 7.3 mm, respectively). At concentration (1000 ppm) showed maximum zone of inhibition (11, 13.8 and 8.6 mm, respectively). Methanol extract, hexane, ethyl acetate and water fraction didnot showed zones of inhibition on E.coli.